From the Community to the Common: Theoretical, Ethical and Political Displacements (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
In this article we interrogate two concepts that are central to current philosophy and social theory: the “community” and “the common”. Our reading hypothesis is that after half a century in force the debate on the question of community began to gradually give way to the debate on the common. In order to explain what we interpret as an epistemological shift, but also an ethical and political one, we undertake an analysis of the uses, meanings and implications of both concepts in a heterogeneous set of contemporary discourses, from Jean-Luc Nancy and Roberto Esposito to Christian Laval and Pierre Dardot, passing through Michael Hardt and Antonio Negri.